A hybrid model of extended FMEA model based on F-PIPRECIA and Z-EDAS methods with Bow Tie to evaluate cybersecurity risks in Industry 4.0 - Ali Memarpour Ghiaci; Jafar Gheidar-Kheljani (مدیریت مهندسی و رایانش نرم)
Cyber security issues have become a complex challenge for companies that obligating to Industry 4.0 paradigm. On the other hand, the concept of cybersecurity in the context of Industry 4.0 proved to be an emerging topic in recent literature. Therefore, in the present study, for the first time, a hybrid FMEA model developed based on multi-criteria decision-making methods in uncertain environments with the Bowtie method in four phases has been used to evaluate cyber security in Industry 4.0. First, based on the literature, 16 cybersecurity risks in the fourth industrial revolution are identified based on the FMEA model and the determinants of RPN are quantified. Then PIPRECIA Fuzzy method was used for weighting the factors and Z-EDAS method for prioritization and critical identification. Finally, Bowtie analysis has been used to analyze these analyses. The result of the proposed implementation has shown its capability and superiority compared to other methods of traditional results such as FMEA and Fuzzy EDAS.